Penerapan Model Pembelajaran Problem Based Learning untuk Meningkatkan Hasil Belajar Siswa Kelas IV Mata Pelajaran IPS Sumber Daya Alam dan Pemanfaatannya di MI Malihatul Hikam - Widianto, Suheri; Danayanti, Fitri Dwi (Awwaliyah: Jurnal Pendidikan Guru Madrasah Ibtidaiyah, 2024)
One way to foster students' enthusiasm and interest in learning is to use learning methods. The learning method that can be applied is the Problem Based Learning method. This type of research data is qualitative and quantitative research. The location in this research is MI Malihatul Hikam. The subjects of this research were class IV B MI Malihatul Hikam for the 2022/2023 academic year, totaling 18 students. The techniques used in data collection are observation, interviews, documentation and tests.Based on the conclusion that the use of the Problem Based Learning model can improve learning outcomes in social studies learning. This can be proven by an increase in learning outcomes in each cycle. In cycle I the average score of the student learning outcomes test was 72.77, the lowest score was 30.00 and the highest score was 85.00. This is known by comparing the pre-cycle value with the first cycle value, the test results show that the first cycle value is greater than the pre-cycle average value, namely 72.77 > 68.88. Meanwhile in cycle II the average value was 74.66, the lowest value was 70.00 and the highest value was 85.00. This is known by comparing the first cycle scores with the second cycle scores, the test results where the second cycle scores are greater than the first cycle scores, the average score is 74.66 > 72.77. And in cycle III the average test result score was 79.16, while the lowest score was 75.00 and the highest score was 85.00. Keywords: Learning Outcomes, Problem Based Learning Models.